Analisis Semiotika Nilai-Nilai Edukasi Dalam Lagu Berencana Itu Keren - Syafruddin Pohan; Nurhasanah Pratiwi (CENDEKIA, 2022)
This paper aims to specifically reveal the signs in the form of educational values contained in the song "Planning is Cool" through a qualitative approach using a descriptive research type of Roland Barthes' semiotic analysis model. The author tries to understand the meanings of reality as well as metaphors in the text of the lyrics of the song "Planning is Cool". Therefore, the subject of this research is the song "Planning is Cool" which is the theme song of the National Family Planning Population Board (BKKBN), and the object of this research is a text document containing the lyrics of the song. The author notes that there are 3 topics of value or educational messages contained in this song, including (1) Self-planning for the future, (2) Self-discipline, (3) Reproductive health for adolescents